2022
DOI: 10.3389/fphar.2022.833584
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Gastric Immune Prognostic Index in Gastric Cancer Patients Treated With PD-1/PD-L1 Inhibitors

Abstract: Objective: This study aimed to investigate the prognostic value of the gastric immune prognostic index (GIPI) in gastric cancer patients treated with programmed death 1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors.Methods: This study was conducted to elucidate the role of GIPI using the data from 146 gastric cancer patients treated with PD-1/PD-L1 inhibitors between August 2016 and December 2020 in Harbin Medical University Cancer Hospital. The GIPI calculation was based on dNLR and LDH. Patients were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The combination of dNLR and LDH, also known as LIPI, was first revealed as a prognostic factor for advanced NSCLC patients treated with immune checkpoint inhibitors (20). More and more studies indicated that LIPI was associated with therapeutic outcomes in many malignancies (14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, there is a lack of researches exploring the value of preoperative LIPI in the outcomes of resectable PDAC patients treated with radical surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of dNLR and LDH, also known as LIPI, was first revealed as a prognostic factor for advanced NSCLC patients treated with immune checkpoint inhibitors (20). More and more studies indicated that LIPI was associated with therapeutic outcomes in many malignancies (14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, there is a lack of researches exploring the value of preoperative LIPI in the outcomes of resectable PDAC patients treated with radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been growing interest in extra-pulmonary cancer. LIPI has been reported to be predictive of the benefit of immunotherapy in other solid tumors (26,27). It was also related to the prognosis of patients with osteosarcoma receiving standard treatment (28), esophageal squamous cell carcinoma undergoing curative surgery (29) or chemoradiotherapy (30), urothelial bladder cancer receiving radical cystectomy (31), and advanced breast cancer patients treated with trastuzumab emtansine (14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the KEYNOTE-059 trial showed that, in metastatic GC or gastroesophageal junction cancer, the e cacy (ORR: 15.5% vs.6.4%) and the median duration of response (16.3 vs. 8.4 months) of patients with positive PD-L1 expression was far better than that of patients with negative PD-L1 expression [41]. Likewise, several studies have demonstrated that PD-L1 expression alone, or with other factors, is positively associated with the clinical bene ts of PD-1/PD-L1 inhibitors [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“… 86 , 87 A cutting‐edge treatment for GC involves inhibiting immunological checkpoints and targeting the PD‐1 pathway. 88 When the combined positive score (the number of PD‐L1‐positive cells, including tumor cells, macrophages, and lymphocytes, divided by the total number of viable tumor cells, multiplied by 100) is one or higher, tumors are deemed to be PD‐L1‐positive. 89 …”
Section: Gc Biomarkers and Their Rolementioning
confidence: 99%